Prevention of Serious Complications during Endoscopic Ultrasound-Guided Biliary Drainage: A Case-Based Technical Review - Rana, Surinder Singh; Shah, Jimil; Bhujade, Harish; Gorsi, Ujjwal; Kang, Mandeep; Gupta, Rajesh (Journal of Digestive Endoscopy, 2022)
Endoscopic ultrasound-guided biliary drainage (EUS-BD) has a potential risk of clinically significant adverse events including fatal complications. Learning from complications improves the results from interventional procedures especially the high-risk procedure like EUS-BD. The various complications that have been reported following EUS-BD include bile leak, bleeding, cholangitis, peritonitis, stent migration both internal and external as well as in the peritoneal cavity and fatal perforations. In this technical review, we discuss technical strategies to prevent serious adverse events during EUS-BD using a case based approach.
Keywords: endoscopic ultrasound; stent; biliary drainage; endoscopic retrograde cholangiopancreatography